MENGENAL LEBIH DEKAT MUSIK ORKESTRA (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2009)
Orchestra is the most popular instrumental music group in Western. As other bigcities in the world, Jakarta also has some orchestras as the result of culturaldiffusion influence. The growth of orchestra in Indonesia is not as good as that inWestern, however, the presence of orchestra in Indonesia has aroused variouscultural phenomenons. The gathering of sixty to seventy musicians and evenmore in an orchestra can form a new community. The cooperation intertwinedwithin the community can create a beautiful and fascinating musicalperformance. A high music quality of an orchestra will not emergeunintentionally without adeguate mastery of the skill. Some of these issues willbe important point in this discussion.Kata kunci: orkestra, komunitas, penampilan